When Everything Revolves Around Internal Carotid Artery: Analysis of Different Management Strategies in Patients With Very Advanced Cancer Involving the Skull Base - Orlandi, Ester; Ferrari, Marco; Lafe, Elvis; Preda, Lorenzo; Benazzo, Marco; Vischioni, Barbara; Bonora, Maria; Rampinelli, Vittorio; Schreiber, Alberto; Licitra, Lisa; Nicolai, Piero (Frontiers in Oncology, 2021)
Internal or common carotid artery encasement (CAE) is observed in almost 2-7% of head and neck cancers (HNC) and designates the tumor with the T4b category. This clinical scenario is associated with a dismal prognosis, owing to the risk for thrombosis and bleeding that usually characterizes such an advanced cancer. Standardized radiological criteria to infer invasion of the carotid artery are lacking. Complete surgical resection in the context of a multimodality treatment is supposed to offer the greatest chances of cure. Surgery can either be carotid-sparing or include carotidectomy. Data on probability of cerebrovascular and non-cerebrovascular complications, risk of carotid blowout, poor oncologic outcomes, and less-than-certain efficacy of diagnostic and interventional preventive procedures against cerebral infarction make it difficult to define surgery as the recommended option among other therapeutic strategies. Non-surgical therapies based on radiation therapy possibly combined with chemotherapy are more frequently employed in HNC with CAE. In this context, carotid blowout is the most feared complication, and its probability increases with tumor stage and cumulative radiation dose received by the vessel. The use of highly conformal radiotherapies such as intensity-modulated particle therapy might substantially improve the manageability of HNC with CAE by possibly reducing the risk of late sequalae. Despite evidence is frail, it appears logical that a case-by-case evaluation through multidisciplinary decision making between head and neck surgeons, radiation oncologists, medical oncologists, diagnostic and interventional radiologists, and vascular surgeons are of paramount value to offer the best therapeutic solution to patients affected by HNC with CAE.